2003
DOI: 10.1002/gea.10090
|View full text |Cite
|
Sign up to set email alerts
|

Colluvial deposits in dry valleys of southern England as proxy indicators of paleoenvironmental and land‐use change

Abstract: Investigations of colluvial sequences infilling the dry valleys of the southern English chalk escarpment have been undertaken since the late 1950s. Chalkland environments are characterized by a rich prehistoric cultural record and, because of poor pollen preservation in the highly calcareous chalkland sediments, molluscan analysis of such deposits has frequently been undertaken to reconstruct past land use and environment. Archaeologists often base their interpretations of past chalkland environments on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Already before the medieval period the Pleistocene loess and Holocene soils were stripped off the slope completely. Studies on valley fills also revealed the long-term impact of agriculture on north-western European landscapes: Wilkinson (2003) investigated colluvial sequences infilling dry valleys of chalk escarpments in southern England. He shows that different spatial and temporal patterns of sedimentation are due to regional variations in past land use, storm impact and topography.…”
Section: North-western Europementioning
confidence: 99%
“…Already before the medieval period the Pleistocene loess and Holocene soils were stripped off the slope completely. Studies on valley fills also revealed the long-term impact of agriculture on north-western European landscapes: Wilkinson (2003) investigated colluvial sequences infilling dry valleys of chalk escarpments in southern England. He shows that different spatial and temporal patterns of sedimentation are due to regional variations in past land use, storm impact and topography.…”
Section: North-western Europementioning
confidence: 99%
“…Cette forte incision résulte de l'augmentation des précipitations et des débits associée au déclin de la fourniture sédimentaire liée à l'arrêt de la cryoclastie (Pastre et al, 2003). Les différences entre bassins versants peuvent s'expliquer par les conditions locales comme l'a montré K. N. Wilkinson (2003) pour les vallons secs du sud de l'Angleterre. Les matériaux issus de l'incision tardiglaciaire ne se retrouvent pas dans les têtes de vallon car ils ont été exportés vers l'aval.…”
Section: Incision Tardiglaciaireunclassified
“…Human settlement of the research area, followed by forest clearance and introduction of agriculture, triggered water soil erosion on slope and redeposition at footslopes and in dry valleys (Starkel, 1988(Starkel, , 2005Bork, 1989;Klimek, 2003;Zolitschka et al, 2003;Wilkinson, 2003). Numerous studies show a good correlation between radiocarbon age of colluvium and settlement stages (Sinkiewicz, 1993(Sinkiewicz, , 1998Twardy, 2002;Lang, 2003).…”
Section: Introductionmentioning
confidence: 99%